Leg restlessness and hyperparathyroidism in Parkinson's disease, a further clue to RLS pathogenesis? - Marano, Massimo; Pozzilli, Valeria; Magliozzi, Alessandro; Tabacco, Gaia; Naciu, Anda Mihaela; Palermo, Andrea; Di Lazzaro, Vincenzo (Frontiers in Neurology, 2023)
Background Non-motor manifestations are the main features of Parkinson's disease (PD). These have been associated with vitamin D abnormalities, but the role of parathormone (PTH) is still obscure. Among the non-motor symptoms of PD, the pathogenesis of restless leg syndrome (RLS) is still debated, but it has been associated with the vitamin D/PTH axis in other disease models. Our study deepens the association between vitamin D and PTH with the prevalence of non-motor symptoms of PD and explores such a relationship in patients reporting leg restlessness. Methods Fifty patients with PD were extensively investigated with motor and non-motor scales. Data on serum levels of vitamin D, PTH, and related metabolites were obtained, and patients were stratified as having vitamin D deficiency or hyperparathyroidism according to standardized criteria. Results Overall, 80% of patients with PD exhibited low vitamin D levels, and hyperparathyroidism was diagnosed in 45%. The analysis of the non-motor symptoms profile using the non-motor symptom questionnaire (NMSQ) revealed 36% of leg restlessness, a main feature of RLS. This was significantly associated with worse motor symptoms, quality of sleep, and quality of life. Moreover, it was associated with hyperparathyroidism (OR: 3.48) and with PTH levels, independent of vitamin D, calcium/phosphate levels, and motor status. Conclusion Our results suggest a significant association between the vitamin D/PTH axis and leg restlessness in PD. PTH has a putative role in nociceptive modulation, and previous evidence on hyperparathyroidism has suggested a possible interrelation with RLS. Further investigations are necessary to add PTH to the non-dopaminergic non-motor landscape of PD.